Building Legal Foundation for a Prosperous Indonesia: Insights from MPR-RI Four Pillars - Soesatyo, Bambang; Rajagukguk, Kadir Johnson; Wahyudi, Heri (Faculty of Law, Universitas Sebelas Maret, 2023)
Indonesia is a state that openly engages with the opportunities and challenges of global economic liberalization. Several issues arise when international legal interventions clash with the identity, values, and interests of indonesian nation. Therefore, this study aimed to strengthen the national foundation in facing globalization and and ushering in a prosperous era for Indonesia. This doctrinal study was conducted using a conceptual approach, with the perspective regarding the role of law in economic development. It also examined the importance of robust legal foundation to maintain national stability in the midst of global economic changes. The results showed that national legal development was crucial to realizing aspirations for unity, sovereignty, justice, and prosperity. Four pillars of MPR-RI could serve as a guide for every citizen to foster nationalism in the midst of rapid globalization. Furthermore, the spirit of legal foundation in four pillars could guide the formulation of national policies that accommodated global interests without forsaking the identity, values, and interests of indonesian nation. The idea of four pillars was also developed as the basis for the philosophy of national economic legal development. The results were expected to guide all stakeholders in constructing economic law in Indonesia, thereby achieving prosperity for the entire population.